Relationship between estimated pulse wave velocity and the risk of future sarcopenia in middle-aged and older Chinese adults: evidence from the China Health and Retirement Longitudinal Study - Song, Dingding; Miao, Jianghu; Zhang, Yunzhu; Zhu, Aiguo (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveSarcopenia, common among older adults, is associated with adverse health outcomes. This study explores the relationship between estimated pulse wave velocity (ePWV), a marker of arterial stiffness, and sarcopenia to support the early diagnosis and prevention strategies.MethodsUsing data from two waves (2011 and 2015) of the China Health and Retirement Longitudinal Study (CHARLS), we conducted a nationally representative cohort study. ePWV was calculated at baseline, and sarcopenia was identified based on the Asian Working Group for Sarcopenia (AWGS) 2019 criteria. We used multivariate logistic regression and restricted cubic spline (RCS) analyses to investigate the ePWV-sarcopenia relationship.ResultsAmong 6,639 participants followed for 4 years, 11.1% were diagnosed with sarcopenia. Initial analyses indicated a positive correlation between ePWV and sarcopenia (β = 1.35), which weakened after adjusting for confounders. RCS analysis demonstrated a non-linear relationship (P-non-linear <0.001), with sarcopenia risk peaking at an ePWV of 9.430 m/s. The highest ePWV quartile showed the lowest grip strength, the longest chair stand test time, and the highest sarcopenia prevalence (P < 0.0001).ConclusionsIn middle-aged and elderly Chinese adults, ePWV variations may be linked to sarcopenia risk, potentially serving as a predictive marker. The non-linear relationship indicates complex underlying mechanisms, meriting further research.